Yamada's textbook of gastroenterology - 4 0 16; Wang, Timothy C.; 5 (Hoboken, NJ : Wiley, 2022)
A key change has been a much greater focus on the structure and function of the human microbiome, with implications for health and disease. The textbook has also been expanded to include a section on the role of gastroenterologists in the management of obesity, which is become an increasing component of GI practice. The endoscopic offerings have been bolstered by new chapters on bariatric endoscopy and endoscope reprocessing. Finally, a greater geriatric focus has been achieved by a new chapter on the aging gastrointestinal tract. Despite these new additions, broadening and increasing the scope of the textbook, the overall number of authors and length of the textbook have not increased, with the consolidation and/or elimination of several older chapters, as well as shortening of others. Despite the continued growth and utilization of internet-based sources of information, we strongly believe that textbooks such as this one remain a vital resource for both experienced clinicians and novices to the fields of gastroenterology and hepatology. Information found on the internet in all fields of knowledge continues to exhibit an inconsistent quality, with a lack of sufficient vetting and expert review on many internet sites. A great advantage of the Yamada textbook is that it is both comprehensive and well sourced by expert authors and editors, such that vital information on the widest spectrum of GI and liver diseases, ranging from essential clinical features to the molecular underpinnings, can be found in one convenient location. As such, a comprehensive reference such as this is still a highly dependable and valued source of knowledge--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: 2 -- 0; 6; anatomy & histology. -- Digestive System Diseases.;Digestive System;Digestive System Physiological Phenomena.;Nutrition Disorders.;Gastrointestinal Microbiome. -- 20; 20; 2